Timing of Kindness - Evidence from a Field Experiment - Axel Ockenfels; Dirk Sliwka; Peter Werner (Center for Economic Studies and ifo Institute (CESifo), 2014)
We conduct a field experiment in a naturally occurring labor environment and track whether the performance of workers responds to unexpected wage increases. Specifically, we investigate how the timing of wage increases affects efforts. We find that workers' performance is about 11% higher for the same total wage when their wage is increased in two steps as opposed to a single increase at the outset. Moreover, workers are more honest and are more willing to do voluntary extra work after surprising wage increases compared to a baseline condition without increases.
Keywords: C93; D64; J33; M52; 330; gift exchange; positive reciprocity; field experiment; honesty